“El deporte y la alimentación saludable de los estudiantes en el aula” - Jácome Toaquiza, Mayra Alexandra (2023)
The educational process presents changes that demand new competencies to respond to the needs of today's society, the same that should focus on promoting healthy habits involving physical exercise and healthy eating, since it is an important factor to improve health. The objective of this research work is to promote sports and healthy eating among students to improve their living conditions in the seventh year of the "Luis Napoleón Dillon" Educational School, located in Pujilí Canton, province of Cotopaxi, in the year 2023. The methodology was based on the interpretative approach, since it allowed understanding the reality of the social context in its own nature; it responds to qualitative research; its research design is based on content analysis because it allows investigating the content through the classification of categories; inductive method; the technique was the interview directed to the teacher, parent and student which allowed obtaining valuable information about the study variables. The educational proposal was the design of a guide based on sports practice and healthy eating for students, which has suitable and interesting activities to enhance and develop skills, abilities and skills in students, as well as to promote the importance and care of maintaining a balanced diet. The result is framed in the reflection, product of the deep analysis of the collected data. The realization of this project contributes to the development of sports practice and healthy life in students, which will provoke joy, happiness, motivation and mainly an integrated lifestyle, fundamental for the learning process. In addition, it helps the optimal growth of the child, since they are key to reduce diseases, giving way to the emotional and physical well-being of the child and thus achieve an optimal quality of life.